ANALISIS TERMOHIDROLIK ALIRAN AIR PENDINGIN PADA BERKAS EMPAT PIPA PEMANAS SUSUNAN SEBARIS MENGGUNAKAN PAKET PROGRAM FLUENT V4.25 - Nazar, Reinaldy; Suwono, Aryadi; Soelaiman, T.A Fauzi (Mesin, 1996)
The FLUENT V4.25 program is the CFD (Computational Fluid Dynamics) simulation. It can be used for ï¬uid ï¬ow and heat transfer analyses and others. Regarding the program, the test is needed to know the validity, to verify that the program will give good output. Based on the test using experimental data on four heated parallel rod bundles, the output FL UENT V4.25, it gave a good result, where the differences between calculation and experimental data are not significant. It is expected that the FLUENT V4. 25 program may achieve success in thermo-hydraulic analysis on other similar systems.